ORGINAL ARTICLE Sneddon‘s syndrome as a disorder of small arteries with endothelial cells proliferation: ultrastructural and neuroimaging study - Lewandowska, Eliza; Wierzba-Bobrowicz, Teresa; Wagner, Teresa; Bogusławska, Romana; Rudnicka, Anna; Leszczyńska, Anna; Pasennik, Elżbieta; Lechowicz, Waldemar; Stępień, Tomasz; Kuran, Włodzimierz (Folia Neuropathologica, 2005)
We report a 18-year-old female patient with livedo reticularis and neurological disturbances. CT scan showed two big ischemic focuses in the pons, moreover MRI revealed small disseminated ischemic focuses in the pons and deep structures of both brain hemispheres. MRA demonstrated no changes in the big extracranial and intracranial arteries. Since the clinical data and neuroimaging results suggested Sneddon’s syndrome, the skin and skeletal muscle biopsy was taken to examine. The immunohistochemical and ultrastructural investigations of the skin biopsy revealed a significant reduction of the lumen of the capillaries and small to medium-sized arteries. Cells surrounding the vascular lumen, frequently with multilayer arrangement and their nuclei placed perpendicularly to the lumen, were CD31, CD34, and sporadically SMA positive. At the ultrastructural level, these proliferating cells showed typical features of endothelial cells: abundant intermediate filaments and Weibel-Palade bodies. Between the endothelial cells some junctions were detached as well in the capillaries as in the small arteries. The smooth muscle cells of the small arteries were electron denser than usual and their cytoplasmic protrusions penetrated to the endothelial cells. The ultrastructural picture of some vessels with a considerably narrow lumen was typical of vessels newly formed during angiogenesis. Neuroimaging including TC, MRI, MRA besides histological, immunohistochemical and ultrastructural evaluation may be useful for diagnosis of Sneddon’s syndrome.